BOARD CHARACTERISTICS AND FIRMS’ SPECIFIC VARIABLES ON CAPITAL STRUCTURE OF SHARIA COMPLIANCE FIRMS IN INDONESIA - Ahmad Fadlur Rahman Bayuny; Al Mustafa, Muhammad Ubaidillah; Rani, Lina Nugraha; Hidayah, Binti Khusnul; Redy, Achdiar (Universitas Airlangga, 2024)
This study examines the influence of board characteristics and firm-specific variables on the capital structure of Sharia-compliant companies in Indonesia’s basic materials sector. Utilizing data from 26 non-financial firms between 2007 and 2020, the research applies the Generalized Method of Moments (GMM) to analyze the relationships between board size, independent directors, board of commissioners, and capital structure decisions. The findings reveal that board size has a significant positive impact on leverage, while the presence of independent directors negatively affects debt usage, reflecting their role in promoting prudent financial practices in line with Sharia principles. The board of commissioners also exhibits a negative correlation with leverage, indicating that stronger supervision reduces reliance on debt. Additionally, firm-specific variables such as growth opportunities and non-debt tax shields significantly affect leverage decisions. This study contributes to the literature by offering insights into how governance practices and firm characteristics influence capital structure in Sharia-compliant firms, with implications for both corporate governance and financial management in the basic materials sector.